(untitled) (Research, Society and Development, 2021)
In the production of ceramic bricks, the drying stage has a greater prominence for being substantial in the process, since the quality of the product is directly related to this stage. Drying on solid ceramic bricks with different percentages of diatomite tailings was experimentally carried out in an oven with forced air circulation. The experiments were carried out based on a 2k factorial experimental design as input factors, at air temperatures (60 and 110 °C), the homogeneity of the mixture (30 and 60 min), and the percentage of waste (10 and 30%). From the matrix of results, the influence of the planning parameters on the moisture behavior was statistically analyzed. About the results of the drying process of ceramic bricks, it was concluded that temperature is the main parameter that controls the removal of moisture from the material. It was observed that diatomite tailings reduce water retention in the specimens, with the best results being found for mixtures with 30% tailings. However, the inverse was verified for the homogenization time, with a tendency of greater water retention for longer times.